MINING COMPANIES AND CORPORATE SOCIAL RESPONSIBILITY: LITERATURE REVIEW TO FIND FUTURE RECOMMENDATIONS - Musilatin Nikmah; Mada Aditia Wardhana (Journal of Innovation Research and Knowledge, 2024)
This study explores how mining companies can balance profitability with environmental sustainability and social responsibility to promote long-term economic growth and social stability. This study uses a literature review to examine the impact of mining operations on the environment and local communities, as well as the benefits of sustainable practices and community development initiatives. The results show that mining companies can create win-win situations by implementing sustainable practices, investing in community development, and building strong relationships with stakeholders. The study recommends that mining companies continue to prioritize environmental sustainability and social responsibility, as these efforts not only benefit the regions in which they operate but also increase funding opportunities and support for mutually beneficial projects